The paladin : a spy novel - Ignatius, David, 1950- (W. W. Norton & Company, 2020)
"A daring, high-tech CIA operation goes wrong and is disowned. Without legal protection, Michael Dunne's only recourse is revenge. CIA operations officer Michael Dunne is tasked with infiltrating an Italian news organization that smells like a front for an enemy intelligence service. It is headed by an American journalist, but the self-styled "people's bandits" run a cyber operation unlike anything the CIA has seen before. Fast, slick and indiscriminate, they steal secrets from everywhere and anyone, and exploit them in ways the CIA can neither understand or stop. Dunne knows it is illegal to run a covert op on an American citizen or journalist; but he has never refused an assignment and he has his boss's assurance of protection. Soon after Dunne infiltrates the organization, his cover disintegrates. When news of the operation hits the papers, someone leaks Dunne's extra marital affairs and the CIA leaves him to take the fall. Now a year later and fresh out of jail, Dunne sets out to track down the people who destroyed his life"--Provided by publisher.